# The first term of an infinite G.P. is $1$ and any term is equal to the sum of all the succeeding terms. Find the sum of the infinite series.

Last updated date: 20th Mar 2023

•

Total views: 305.7k

•

Views today: 7.85k

Answer

Verified

305.7k+ views

Hint: Any term in G.P. is equal to the sum of all the succeeding terms. We have:

$ \Rightarrow {T_n} = {T_{n + 1}} + {T_{n + 2}} + {T_{n + 3}} + ......\infty $

The general term of G.P. can be written as:

$ \Rightarrow {T_n} = a{r^{n - 1}} .....(i)$

And according to the information given in the question, any term of the G.P. is equal to the sum of all the succeeding terms. From this we’ll get:

$ \Rightarrow {T_n} = {T_{n + 1}} + {T_{n + 2}} + {T_{n + 3}} + ......\infty $

Substituting corresponding values in equation$(i)$, we’ll get:

$ \Rightarrow a{r^{n - 1}} = a{r^n} + a{r^{n + 1}} + a{r^{n + 2}} + ......\infty ,$

$a$ is the first term of G.P. and its value is $1$ as per the information given in the question. So putting its value, we’ll get:

$

\Rightarrow {r^{n - 1}} = {r^n} + {r^{n + 1}} + {r^{n + 2}} + .....\infty , \\

\Rightarrow {r^{n - 1}} = {r^n}\left[ {1 + r + {r^2} + .....\infty } \right], \\

\Rightarrow \dfrac{1}{r} = \left[ {1 + r + {r^2} + .....\infty } \right] .....(ii) \\

$

Now, the terms on the right hand side of the above equation constitutes an infinite G.P. with $1$ as the first term and $r$ as the common ratio. And we know the formula for sum of terms of infinite G.P.:

$ \Rightarrow {S_\infty } = \dfrac{a}{{1 - r}}$

So, on using this formula for equation $(ii)$,we’ll get:

$

\Rightarrow \dfrac{1}{r} = \dfrac{1}{{1 - r}}, \\

\Rightarrow 1 - r = r, \\

\Rightarrow 2r = 1, \\

\Rightarrow r = \dfrac{1}{2}. \\

$

Thus, the common ratio of the G.P. is $\dfrac{1}{2}$ and its first term is already given as $1$. So, we our infinite G.P.:

$ \Rightarrow 1,\dfrac{1}{2},\dfrac{1}{4},\dfrac{1}{8},.......\infty $

For finding sum of its terms, we will again apply${S_\infty } = \dfrac{a}{{1 - r}}$, we’ll get:

$

\Rightarrow {S_\infty } = \dfrac{1}{{1 - \dfrac{1}{2}}}, \\

\Rightarrow {S_\infty } = 2 \\

$

Therefore, the sum of infinite G.P. is $2$.

Note: If a G.P. consists of infinite terms, then we can only calculate the sum of its terms if it's common ratio is greater than $0$ and less than $1$$\left( {0 < r < 1} \right)$.Otherwise its sum will not be defined.

$ \Rightarrow {T_n} = {T_{n + 1}} + {T_{n + 2}} + {T_{n + 3}} + ......\infty $

The general term of G.P. can be written as:

$ \Rightarrow {T_n} = a{r^{n - 1}} .....(i)$

And according to the information given in the question, any term of the G.P. is equal to the sum of all the succeeding terms. From this we’ll get:

$ \Rightarrow {T_n} = {T_{n + 1}} + {T_{n + 2}} + {T_{n + 3}} + ......\infty $

Substituting corresponding values in equation$(i)$, we’ll get:

$ \Rightarrow a{r^{n - 1}} = a{r^n} + a{r^{n + 1}} + a{r^{n + 2}} + ......\infty ,$

$a$ is the first term of G.P. and its value is $1$ as per the information given in the question. So putting its value, we’ll get:

$

\Rightarrow {r^{n - 1}} = {r^n} + {r^{n + 1}} + {r^{n + 2}} + .....\infty , \\

\Rightarrow {r^{n - 1}} = {r^n}\left[ {1 + r + {r^2} + .....\infty } \right], \\

\Rightarrow \dfrac{1}{r} = \left[ {1 + r + {r^2} + .....\infty } \right] .....(ii) \\

$

Now, the terms on the right hand side of the above equation constitutes an infinite G.P. with $1$ as the first term and $r$ as the common ratio. And we know the formula for sum of terms of infinite G.P.:

$ \Rightarrow {S_\infty } = \dfrac{a}{{1 - r}}$

So, on using this formula for equation $(ii)$,we’ll get:

$

\Rightarrow \dfrac{1}{r} = \dfrac{1}{{1 - r}}, \\

\Rightarrow 1 - r = r, \\

\Rightarrow 2r = 1, \\

\Rightarrow r = \dfrac{1}{2}. \\

$

Thus, the common ratio of the G.P. is $\dfrac{1}{2}$ and its first term is already given as $1$. So, we our infinite G.P.:

$ \Rightarrow 1,\dfrac{1}{2},\dfrac{1}{4},\dfrac{1}{8},.......\infty $

For finding sum of its terms, we will again apply${S_\infty } = \dfrac{a}{{1 - r}}$, we’ll get:

$

\Rightarrow {S_\infty } = \dfrac{1}{{1 - \dfrac{1}{2}}}, \\

\Rightarrow {S_\infty } = 2 \\

$

Therefore, the sum of infinite G.P. is $2$.

Note: If a G.P. consists of infinite terms, then we can only calculate the sum of its terms if it's common ratio is greater than $0$ and less than $1$$\left( {0 < r < 1} \right)$.Otherwise its sum will not be defined.

Recently Updated Pages

Calculate the entropy change involved in the conversion class 11 chemistry JEE_Main

The law formulated by Dr Nernst is A First law of thermodynamics class 11 chemistry JEE_Main

For the reaction at rm0rm0rmC and normal pressure A class 11 chemistry JEE_Main

An engine operating between rm15rm0rm0rmCand rm2rm5rm0rmC class 11 chemistry JEE_Main

For the reaction rm2Clg to rmCrmlrm2rmg the signs of class 11 chemistry JEE_Main

The enthalpy change for the transition of liquid water class 11 chemistry JEE_Main

Trending doubts

Difference Between Plant Cell and Animal Cell

Write an application to the principal requesting five class 10 english CBSE

Ray optics is valid when characteristic dimensions class 12 physics CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Write the 6 fundamental rights of India and explain in detail

Write a letter to the principal requesting him to grant class 10 english CBSE

List out three methods of soil conservation

Fill in the blanks A 1 lakh ten thousand B 1 million class 9 maths CBSE

Write a letter to the Principal of your school to plead class 10 english CBSE